Registered nurse staffing mix and quality of care in nursing homes: A longitudinal analysis - Kim, H.; Harrington, C.; Greene, William (Gerontological Society of America, 2009)
Purpose: To examine the relationship between registered nurse (RN) staffing mix and quality of nursing home care measured by regulatory violations. Design and Methods: A retrospective panel data study (1999-2003) of 2 groups of California freestanding nursing homes. One group was 201 nursing homes that consistently met the state's minimum standard for total nurse staffing level over the 5-year period. The other was 210 nursing homes that consistently failed to meet the standard over the period. All facility and market variables were drawn from California's cost report data and state licensing and certification data, as well as 3 other databases. Results: The RN to total nurse staffing ratio was negatively related to serious deficiencies in nursing homes that consistently met the staffing standard, whereas the ratio was negatively associated with total deficiencies in nursing homes that consistently failed to meet the standard over the 5-year period. As the RN to licensed vocational nurse ratios increased, total deficiencies and serious deficiencies decreased in both groups of nursing homes. Implications: A higher RN mix is positively related to quality of care, but the relationship is affected by overall nurse staffing levels in nursing homes. Further studies are necessary for a better understanding of RNs' unique contributions to the quality of care in nursing homes.